Merkel cell carcinoma of an atypical presentation: A case report and literature review - Layla Tahiri Elousrouti; Khawla Aabdellaoui; Imane Gouzi; Sara Elloudi; Hanane Baybay; Fatimazahra Elemernissi; Nawal Hammas; Hinde Elfatemi; Laila Chbani (Our Dermatology Online, 2022)
Merkel cell carcinoma (MCC) is a primary cutaneous neuroendocrine carcinoma. It is a rare and aggressive tumor characterized by a high frequency of local recurrence, regional nodal metastasis, distant metastasis, and a low survival rate. Its diagnosis is challenging due to its rarity and it may be clinically mistaken for other skin cancers. It requires an incisional biopsy and confirmation by histology and immunohistochemical staining. This case illustrates an uncommon presentation of MCC in a 53-year-old young adult in an unexposed area of the right gluteal region. It is a rare cutaneous tumor that should be diagnosed and treated precociously given the aggressive nature of MCC and the limited therapeutic options for metastatic tumors. Herein, we urge physicians to suspect this diagnosis in front of any rapidly growing skin tumor, even in an unusual location, to provide the patient with appropriate treatment and improve the overall survival rate.